Associations of nutritional status and dietary habits with the development of female infertility. A case–control study - Martín-Manchado, Laura; Moya-Yeste, Antonio Manuel; Sánchez-Sansegundo, Miriam; Hurtado-Sánchez, José Antonio; Gil-Miralles, Regina Andrea; Tuells, José; Zaragoza-Martí, Ana (Frontiers in Nutrition, 2024)
Female infertility is a complex condition influenced by multiple factors, including lifestyle factors. This case-control study aimed to analyze the association between nutritional status, dietary habits, and infertility in women from the province of Alicante. Conducted in various health centers and hospitals in Alicante, Spain, the study included 60 infertile women and 30 fertile women, all between 18 and 40 years old, selected through consecutive sampling. The results indicated that infertile women had lower muscle mass (p=0.005) and larger hip circumference (p=0.034) compared to fertile women. Additionally, a significant association was observed between high red meat consumption and an increased risk of female infertility (p=0.011). These findings suggest that body composition and dietary habits may be important factors in the evaluation and treatment of female infertility. Interventions focused on increasing muscle mass, reducing localized body fat, and modifying the diet to decrease red meat consumption could be beneficial for female fertility. Future research should explore these findings in longitudinal studies and across different populations to confirm their validity.